US Adult Rheumatologists' Perspectives on the Transition Process for Young Adults With Rheumatic Conditions. Issue 3 (27th February 2020) - Zisman, Devy; Samad, Aaida; Ardoin, Stacy P.; Chira, Peter; White, Patience; Lavi, Idit; von Scheven, Emily; Lawson, Erica F.; Hing, Melinda; Mellins, Elizabeth D.
Abstract : Objective: To assess the attitudes and common practices of adult rheumatologists in the US regarding health care transition (HCT) for young adults with rheumatic diseases. Methods: An anonymous online survey was sent to US adult rheumatologist members of the American College of Rheumatology to collect demographic data and information on attitudes and common practices regarding the transition process. Results: Of 4, 064 contacted rheumatologists, 203 (5%) completed the survey. Almost half of respondents (45.1%) were never trained in transition practices, and 74.7% were not familiar with the American Academy of Pediatrics/American Academy of Family Physicians/American College of Physicians Consensus Statement About Transitions for Youth with Special Healthcare Needs. Only 56.2% felt comfortable caring for former pediatric patients. The vast majority of respondents (90.7%) did not have a multidisciplinary transition team, and 37% did not have a plan for transitioning pediatric patients into their practice. Most adult rheumatologists were unsatisfied with the current transition process (92.9%), due to insufficient resources, personnel (91.1%), and time in clinic (86.9%). They also were unsatisfied with referral data received concerning previous treatments (48.9%), hospitalization history (48%), disease activity index (45.1%), medical history summary (43.9%), comorbidities (36.4%), medication list (34.1%), and disease classification (32.6%). Three major barriers to HCT were lack of insurance reimbursement (33.7%), knowledge about community resources (30.8%), and lapses in care between primary provider and specialist (27.8%). Conclusion: This survey identified substantial gaps in knowledge and resources regarding HCT for young adults with rheumatic diseases. These may be best addressed by further training, research, dedicated resources, adequate payment, and practice guidelines.